2020
DOI: 10.1111/bcp.14342
|View full text |Cite
|
Sign up to set email alerts
|

Reporting rates of adverse reactions to specialty care medicines exhibit a direct positive correlation with patient exposure: A lack of evidence for the Weber effect

Abstract: The classical Weber effect describes an increase in adverse reaction (AR) reports after medicinal product authorisation, with a peak in AR reporting at the end of the second year followed by a decline, despite increasing patient exposure. The present study aimed to evaluate the validity of the Weber effect in the context of authorised medicines in a specialty care setting. Methods: Using 6-monthly sales data as a proxy for exposure, the exposure-adjusted reporting rates for AR reports for 10 selected specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Indeed, in our study, the date of labeling was not significantly associated with the adverse event reporting rate in pharmacovigilance databases. This finding is consistent with previous studies exploring Weber's effects, which have found no evidence of this phenomenon in recent years [3]. Surprisingly, the reporting rate of certain drugs, such as desloratadine, was particularly low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, in our study, the date of labeling was not significantly associated with the adverse event reporting rate in pharmacovigilance databases. This finding is consistent with previous studies exploring Weber's effects, which have found no evidence of this phenomenon in recent years [3]. Surprisingly, the reporting rate of certain drugs, such as desloratadine, was particularly low.…”
Section: Discussionsupporting
confidence: 92%
“…While disproportionality analyses allow the detection of higher than expected associations between adverse events and drugs, the lack of patient exposure data and the selective reporting of adverse events do not allow the calculation of adverse event incidence rates [2]. Yet, despite this selective reporting, a recent study suggested that the total number of adverse events reported for a given drug is correlated to drug exposure without evidence of the Weber effect or other time-varying reporting bias [3]. This total number of reported adverse events cannot be used as a proxy for drug exposure per se, given drugs display heterogeneous safety profiles, different indications, and exposed populations, but we hypothesized that it could be the case among a drug class.…”
Section: Introductionmentioning
confidence: 99%
“…Rucaparib, niraparib and talazoparib are all black triangle drugs and all suspected ADRs need to be reported regardless of severity. There is likely to be a significant under‐reporting of suspected ADRs 50,51 …”
Section: Discussionmentioning
confidence: 99%
“…Combining EC and DL can shorten the data transmission time and improve security performance. The advent of the “Internet +” era has provided an opportunity for the rapid development of Mobile Intelligence (MI) and EC ( Han et al, 2019 ; Modgill et al, 2020 ). In particular, EC is a technology developed under the background of high bandwidth, time-sensitive, and integrated Internet of Things (IoT), much different from Cloud Computing (CC).…”
Section: Theory and Methodsmentioning
confidence: 99%